Effects of different plyometric training frequencies on measures of athletic performance in prepuberal male soccer players - Bouguezzi, R.; Chaabene, H.; Negra, Y.; Ramirez-Campillo, R.; Jlalia, Z.; Mkaouer, B.; Hachana, Y. (The Journal of Strength and Conditioning Research, 2020)
This study aimed to compare the effects of 1 vs. 2 sessions of equal-weekly volume plyometric training (PT) across 8 weeks on measures of athletic performance (i.e., sprint time, change of direction [CoD], jumping ability, and muscle strength) in prepuberal male soccer players. Thirty participants were randomly assigned either to 1 session PT group (1SPT [n = 15]) or 2 sessions PT group (2SPT [n = 15]). Plyometric training was integrated into their regular soccer training routine. Pretraining and posttraining tests for the assessment of sprint time (e.g., 5, 10, 20, and 30-m), CoD (e.g., T-test and modified Illinois change of direction test [MICODT]), jumping ability (e.g., standing long jump [SLJ], countermovement jump [CMJ], and squat jump [SJ]), muscle strength (reactive strength index [RSI]), and kicking distance were conducted. Results showed a main effect of time for 5-m sprint-time performance (F(1,56) = 4.00, effect size [ES] = 0.53 [medium], p = 0.05), T-test (F(1,56) = 23.19, ES = 1.28 [large], p < 0.001), MICODT (F(1,56) = 5.72, ES = 0.94 [large], p = 0.02), SLJ (F(1,56) = 16.63, ES = 1.09 [large], p < 0.001), CMJ (F(1,56) = 15.43, ES = 1.04 [large], p < 0.001), SJ (F(1,56) = 20.27, ES = 1.20 [large], p < 0.001), RSI (F(1,56) = 26.26, ES = 1.36 [large], p < 0.001), and kicking distance (F(1,56) = 47.19, ES = 1.83 [large], p < 0.001). There were no training group × time interactions in all the measured outcomes. In conclusion, when an equated moderate volume of jumps is performed, higher PT frequency across 8 weeks has no extra effects on prepuberal male soccer players' measures of athletic performance. The present findings may help optimizing PT interventions dedicated to prepuberal male soccer players.